Hubungan Peran Bidan, Dukungan Suami, dan Akses Informasi dengan Kecemasan Ibu Hamil Usia Remaja dalam Menghadapi Persalinan di Puskesmas Johar Baru - Sari Wulandari; Siti Syamsiah; Risza Khoirunnisa (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Pregnancy experienced by teenagers is the first experience, so the third trimester is felt to be even more worrying because it is getting closer to the delivery process. Mothers will tend to feel anxious about their pregnancy, feel anxious, and afraid of facing childbirth. Purpose to determine the relationship between the role of midwives, husband's support, and access to information with the anxiety of teenage pregnant women in facing childbirth at the Johar Baru Health Center. Type of quantitative research with cross sectional research design. The research sample was 40 third-trimester pregnant women in their teens who made ANC visits at the Johar Baru Health Center, which were taken using a simple random sampling technique. Data obtained by distributing questionnaires. Univariate and bivariate data analysis with chi-square test. The results of univariate analysis obtained that the majority of respondents experienced moderate anxiety, namely 60.0% of pregnant women, the majority of respondents were in the role of a good midwife, namely 57.5% of pregnant women, the majority of respondents had good husband support, namely 60.0% of pregnant women , and the majority of respondents have good access to information, namely 52.5% of pregnant women. The results of the bivariate analysis showed that the relationship between the midwife's role and the anxiety of teenage pregnant women obtained a p-value of 0.016. The relationship between husband's support and the anxiety of teenage pregnant women obtained a p-value of 0.007. The relationship between access to information and the anxiety of teenage pregnant women obtained a p-value of 0.012. There is a relationship between the role of midwives, husband's support, and access to information with the anxiety of teenage pregnant women in facing childbirth at the Johar Baru Health Center in 2022. Keywords : Anxiety, Childbirth, Adolescents ABSTRAK Kehamilan yang dialami usia remaja merupakan pengalaman pertama kali, sehingga trimester III dirasakan semakin mencemaskan karena semakin dekat dengan proses persalinan. Ibu akan cenderung merasa cemas dengan kehamilannya, merasa gelisah, dan takut menghadapi persalinan. Tujuan untuk mengetahui hubungan peran bidan, dukungan suami, dan akses informasi dengan kecemasan ibu hamil hamil usia remaja dalam menghadapi persalinan di Puskesmas Johar Baru. Jenis penelitian kuantitatif dengan desain penelitian cross sectional. Sampel penelitian adalah 40 ibu hamil trimester III pada usia remaja yang melakukan kunjungan ANC di Puskesmas Johar Baru yang diambil dengan teknik simple random sampling. Data diperoleh dengan cara membagikan kuesioner. Analisa data secara univariat dan bivariat dengan uji chi-square. Hasil analisis univariat diperoleh mayoritas responden mengalami cemas sedang yaitu 60,0% ibu hamil, mayoritas responden berada dalam peran bidan yang baik yaitu 57,5% ibu hamil, mayoritas responden memiliki dukungan suami yang baik yaitu 60,0% ibu hamil, dan mayoritas responden memiliki akses informasi yang baik yaitu 52,5% ibu hamil. Hasil analisis bivariat diperoleh hubungan peran bidan dengan kecemasan ibu hamil usia remaja diperoleh p-value sebesar 0,016. Hubungan dukungan suami dengan kecemasan ibu hamil usia remaja diperoleh p-value sebesar 0,007. Hubungan akses informasi dengan kecemasan ibu hamil usia remaja diperoleh p-value sebesar 0,012. Ada hubungan peran bidan, dukungan suami, dan akses informasi dengan kecemasan ibu hamil usia remaja dalam menghadapi persalinan di Puskesmas Johar Baru Tahun 2022. Kata kunci: Kecemasan, Persalinan, Remaja